2019
DOI: 10.1111/joa.13004
|View full text |Cite
|
Sign up to set email alerts
|

Vascular coverage of the anterior knee region – an anatomical study

Abstract: Descriptions of vessel angiosomes or perforasomes throughout the human body are quite frequent, and led to the development of flaps nowadays commonly used to surgically cover skin and soft tissue defects. In these procedures, the surgeon requires a profound anatomical knowledge of the respective blood vessels and the extent of the perfused area to define the size of the graft. In the region of the knee joint, descriptions of flaps based on the superior lateral genicular artery and descending genicular artery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The DGA originates from the superficial femoral artery at the level of the adductor hiatus (11.9–17 cm above the joint line) and has a robust branching system that includes the saphenous artery, muscular branches, and osteoarticular branches. 5 , 6 The superomedial genicular artery originates from the popliteal artery at an average of 4 cm above the medial condyle, 2 cm medial to the longitudinal axis of the leg. The origin of the saphenous artery is variable and may be absent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DGA originates from the superficial femoral artery at the level of the adductor hiatus (11.9–17 cm above the joint line) and has a robust branching system that includes the saphenous artery, muscular branches, and osteoarticular branches. 5 , 6 The superomedial genicular artery originates from the popliteal artery at an average of 4 cm above the medial condyle, 2 cm medial to the longitudinal axis of the leg. The origin of the saphenous artery is variable and may be absent.…”
Section: Methodsmentioning
confidence: 99%
“…When present, it may arise as a branch of the DGA or originate directly from the femoral or popliteal artery. 6 These serve as a reliable source of skin perforators for flaps in the medial knee and distal thigh, with a highly variable angiosome area. Furthermore, many anastomoses exist between these arteries in this region.…”
Section: Methodsmentioning
confidence: 99%
“…Creation of skin flaps at an acute angle of less than 60° at the intersection of other incisions is a risk for the blood supply. 11 Short skin bridges of less than 6–7 cm between incisions are not recommended. In complex situations with multiple incisions or skin adherence, plastic surgeons should be involved for skin incision design and for muscle flap procedures.…”
Section: Surgical Approachmentioning
confidence: 99%
“…GAE attempts to target and inhibit angiogenesis that occurs from the proinflammatory state in knee OA. To achieve this, there are 6 vessels that are typically targeted during GAE, which include the medial superior genicular artery, medial inferior genicular artery, lateral superior genicular artery, lateral inferior genicular artery, descending genicular artery, and anterior tibial recurrent artery (36)(37)(38)(39). Studies have demonstrated that all 6 arteries are present in most patients, with asymmetry in size between vessels and collateralization of supply across the joint being both been reported (36)(37)(38).…”
Section: Gae (Anatomy and Mechanism Of Effect)mentioning
confidence: 99%